Prevalence and Determinants of Smoking among Young Age Male Patients Coming at OPD in Selected Hospital (Medicine Today, 2017)
Smoking is now recognized as a major public health problem in the developing world. Bangladesh is one of the largest populated developing country. Here public health crisis is in danger among youngers. The study was conducted among the young age male patients in selected hospital based on broad objective of exploring the prevalence and determinants of smoking behavior of young age male patients. A cross sectional descriptive study was conducted on prevalence of young age patients in selected hospital. The quantitative investigation was undertaken to fulfill the objectives of the study by collecting information using questionnaire. Findings of the study showed that 35.33% of respondents have smoking habit. We also found that about 86.79% smoking habit respondents start smoking when they were 14-17 years old. The study tried to find out current adolescent smoking trend in rural area of developing country. In our study we know that most of the smoker started smoking at their adolescent period & it is a high prevalence. There is a significant association between smoking and other risky behavior like Cannabis, Yaaba, Alcohol etc. So urgently our Govt. need to implement public health interventions, with special attention to the determinants of smoking in this age group.Medicine Today 2017 Vol.29(2): 38-41